2022
DOI: 10.1186/s12872-022-02969-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of (sdLDLc*HCYc)/HDLc ratio in clinical auxiliary diagnosis of primary cerebral infarction

Abstract: Background Timely detection of cerebral infarction is of vital importance in planning intervention effect of rapid rehabilitation. The clinical auxiliary diagnosis value of single biomarker, including small dense low-density lipoprotein concentration (sdLDLc), homocysteine concentration (HCYc) and high-density lipoprotein cholesterol concentration (HDLc) for cerebral infarction has been confirmed by many studies. Whether the use of three biomarkers in combination by calculating (sdLDLc*HCYc)/HD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Previous studies also have suggested that LDL-C-to-HDL-C ratio is significantly correlated with acute coronary syndromes 28 . Luo et al 29 suggested that a higher SHR was significantly associated with an increased presence of carotid plaques. To our knowledge, it is the first study to assess the relationship between SHR and MAFLD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies also have suggested that LDL-C-to-HDL-C ratio is significantly correlated with acute coronary syndromes 28 . Luo et al 29 suggested that a higher SHR was significantly associated with an increased presence of carotid plaques. To our knowledge, it is the first study to assess the relationship between SHR and MAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Luo et al . 29 suggested that a higher SHR was significantly associated with an increased presence of carotid plaques. To our knowledge, it is the first study to assess the relationship between SHR and MAFLD.…”
Section: Discussionmentioning
confidence: 99%